2018
DOI: 10.1242/jeb.187427
|View full text |Cite
|
Sign up to set email alerts
|

Encoding lateralization of jump kinematics and eye use in a locust via bio-robotic artifacts

Abstract: The effect of previous exposure to lateral sensory stimuli in shaping the response to subsequent symmetric stimuli represents an important overlooked issue in neuroethology, with special reference to arthropods. In this research, we investigated the hypothesis to 'programme' jumping escape direction as well as surveillance orientation in young and adult individuals of Locusta migratoria as an adaptive consequence of prior exposure to directional-biased predator approaches generated by a robotic leopard gecko r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 117 publications
(131 reference statements)
0
42
0
1
Order By: Relevance
“…In the past, a variety of studies focused on living organisms interaction with robotic cues [31][32][33][34] and controlling the robot through BCI, but there have been few research on the control of teleoperation robot based on motor imagery EEG. Meanwhile, most of the previous research groups focus on the conventional two class or four class classification from EEG signals to get one or four control commands.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a variety of studies focused on living organisms interaction with robotic cues [31][32][33][34] and controlling the robot through BCI, but there have been few research on the control of teleoperation robot based on motor imagery EEG. Meanwhile, most of the previous research groups focus on the conventional two class or four class classification from EEG signals to get one or four control commands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that robots can be used to influence the response of animal in longitudinal studies with sequential exposure to robotic stimuli. For example, Locusts (Locusta migratoria) learned to escape preferentially on a side, following exposure to a robotic Gecko coming from the opposite side (Romano et al, 2019b). In our case, the robot is used to proxy a trained conspecific that acts as a demonstrator in a social learning task, while in the study by Romano et al (2019b) a robotic predator served as aversive stimulus to condition the subjects spatially.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Locusts (Locusta migratoria) learned to escape preferentially on a side, following exposure to a robotic Gecko coming from the opposite side (Romano et al, 2019b). In our case, the robot is used to proxy a trained conspecific that acts as a demonstrator in a social learning task, while in the study by Romano et al (2019b) a robotic predator served as aversive stimulus to condition the subjects spatially. Our experimental paradigm could serve as inspiration to design similar studies in other species.…”
Section: Discussionmentioning
confidence: 99%
“…us, it was imitated in this work. Locusts can not only jump forward but also jump laterally [50]. In this paper, only the jumping of locust in a plane is studied.…”
Section: Mechanism Design and Performance Analysismentioning
confidence: 99%